Lithiumniobate die assembled by a low-stress soldering technique method to fasten a surface acoustic wave sensor - Ribes-Pleguezuelo, Pol; Frei, Katherine; Bruckner, Gudrun; Beckert, Erik; Eberhardt, Ramona; Tünnermann, Andreas (PHOTOPTICS 2018 - Proceedings of the 6th International Conference on Photonics, Optics and Laser Technology, 2017)
Solderjet bumping technique was applied to assemble a Surface Acoustic Wave (SAW) sensor prototype designed with a lithiumniobate crystal and a base sub-mount made of stainless steel. The assembly was designed with this technology in order to withstand the device’s mechanical strength requirements. The initial performed tests showed that the solderjet bumping technique can be used to assemble brittle components without creating internal damage in the crystal. The selected solder alloy Au80Sn20 used to fasten the lithiumniobate showed proper alloy wettability and joint strength on the crystal and on the substrate material. Finally, a lithiumniobate die device was soldered by soldering means to the stainless steel sub-mount, and withstood the strength device requirements by passing robustness (push) tests.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Lithiumniobate; Optical Crystal; Packaging; Solderjet Bumping Technique; Surface Acoustic Wave Sensor